2008
DOI: 10.1152/japplphysiol.00681.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss on lactate transporter expression in skeletal muscle of obese subjects

Abstract: DR. Effect of weight loss on lactate transporter expression in skeletal muscle of obese subjects. J Appl Physiol 104: 633-638, 2008. First published December 13, 2007 doi:10.1152/japplphysiol.00681.2007.-The effects of weight loss on skeletal muscle lactate transporter [monocarboxylate transporter (MCT)] expression in obese subjects were investigated to better understand how lactate transporter metabolism is regulated in insulin-resistant states. Ten obese subjects underwent non-macronutrient-specific energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…So, the increased lactate and MCT1 levels suggesting an increased lactate transport might be in part associated with the metabolic disease sensitization. On the contrary, obese subjects which present an increased MCT4 protein level in muscle compared to lean subjects exhibited decreased MCT4 levels down to the lean control level when submitted to a weight loss . Concerning MCT1, this study did not describe any change in muscle expression after weight loss.…”
Section: Introductioncontrasting
confidence: 79%
“…So, the increased lactate and MCT1 levels suggesting an increased lactate transport might be in part associated with the metabolic disease sensitization. On the contrary, obese subjects which present an increased MCT4 protein level in muscle compared to lean subjects exhibited decreased MCT4 levels down to the lean control level when submitted to a weight loss . Concerning MCT1, this study did not describe any change in muscle expression after weight loss.…”
Section: Introductioncontrasting
confidence: 79%
“…In diabetic male Wistar rats, monocarboxylate (88). Although this pattern has also been reported in male diabetic patients with decreased skeletal muscle expression of MCT1 (87), obese individuals did not show differences in muscle MCT1 protein concentrations compared with controls (85). Although MCT1 in human hepatic or intestinal tissues was not directly measured in these studies, these may similarly be affected in diseased conditions.…”
Section: Introductionsupporting
confidence: 48%
“…Endurance training reduced BMI in type 2 diabetic men in our study as has already been evidenced in previous work [ 18 ] . The reduction in intracellular MCT-4 proteins may be related to the weight loss of the subjects in our study, since Metz et al [ 20 ] demonstrated that MCT-4 proteins were signifi cantly reduced after weight loss in obese subjects. It is noteworthy that there was no diff erence in MCT-1 expression in their subjects before and after weight loss.…”
mentioning
confidence: 56%